PEMBENTUKAN KOPERASI USAHA MERUPAKAN SOLUSI BAGI PENGEMBANGAN UMKM - Fitrijati, Krisnhoe Rachmi; Widianingsih, Rini; Purwati, Atiek Sri; Pratiwi, Umi; Ulfa, Permata; Suparlinah, Irianing; Sunarmo, Agus (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Business cooperatives are a form of cooperative that focuses on developing small and medium enterprises (MSMEs). This type of cooperative plays an important role in supporting local economic growth and community empowerment. One of the business entities supporting the Indonesian economy is a cooperative. Now cooperatives do not only focus on the financial sector such as savings and loan cooperatives, but cooperatives must start moving in real sectors such as consumer, producer, service and marketing cooperatives. Real sector cooperatives focus on economic activities that produce goods or services that can be consumed or used by their members or the general public. The problems currently faced are limited resources, weak governance, and limited access to technology. The government and other stakeholders need to continue to strive to increase the capacity of cooperatives and create a conducive environment for MSMEs. The solution to overcome this problem is by providing outreach to business actors and the community as well as adequate support, business cooperatives can become effective strategic partners in encouraging